Pengaruh Net Profit Margin, Debt to Equity Ratio, Price Earning Ratio, dan Price to Book Value terhadap Return Saham (Studi Empiris pada Perusahaan Plastik dan Kemasan Kategori Industri Dasar yang Terdaftar di Bursa Efek Indonesia Tahun 2017–2021) - Salsabila, Fadhilah Shafa'; Yantiana, Nella; Fahmi, Muhammad (Undergraduate Program in Accounting, Department of Accounting, Faculty of Economics and Business, Universitas Tanjungpura, 2024)
This study examines the effects of Net Profit Margin, Debt-to-Equity Ratio, Price-Earnings Ratio, and Price-to-Book Value on stock returns in plastic and packaging companies within the basic industry category listed on the Indonesia Stock Exchange during the 2017–2021 period. The study employs a quantitative approach using secondary data obtained from audited annual financial statements and stock-price information. The sample was selected through purposive sampling and consisted of nine companies with 45 initial firm-year observations. After eliminating nine outlier observations, 36 observations were included in the final analysis. Data were analyzed using descriptive statistics, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS version 25. The results show that Net Profit Margin, Debt-to-Equity Ratio, and Price-to-Book Value have positive but insignificant effects on stock returns, while Price-Earnings Ratio has a negative but insignificant effect. Simultaneously, the four independent variables do not significantly affect stock returns. The coefficient of determination is 6.8%, indicating that the research model has limited explanatory power.